Initial Bacterial Adhesion on Different Yttria-Stabilized Tetragonal Zirconia Implant Surfaces in Vitro - Karygianni, Lamprini (Materials (Basel), 2013)
Bacterial adhesion to implant biomaterials constitutes a virulence factor leading to biofilm formation, infection and treatment failure. The aim of this study was to examine the initial bacterial adhesion on different implant materials in vitro. Four implant biomaterials were incubated with Enterococcus faecalis, Staphylococcus aureus and Candida albicans for 2 h: 3 mol % yttria-stabilized tetragonal zirconia polycrystal surface (B1a), B1a with zirconium oxide (ZrO(2)) coating (B2a), B1a with zirconia-based composite coating (B1b) and B1a with zirconia-based composite and ZrO(2) coatings (B2b). Bovine enamel slabs (BES) served as control. The adherent microorganisms were quantified and visualized using scanning electron microscopy (SEM); DAPI and live/dead staining. The lowest bacterial count of E. faecalis was detected on BES and the highest on B1a. The fewest vital C. albicans strains (42.22%) were detected on B2a surfaces, while most E. faecalis and S. aureus strains (approximately 80%) were vital overall. Compared to BES; coated and uncoated zirconia substrata exhibited no anti-adhesive properties. Further improvement of the material surface characteristics is essential.